(untitled) (Research, Society and Development, 2021)
The use of electronic devices such as cell phones, tablets, remote controls, notebooks, computers was intensified during the Covid-19 pandemic, where a large part of the population used remote services, abdicating face-to-face services, such as banking services, online shopping, orders, deliveries, education, as a way to keep distance. The present work aimed to indicate the main microorganisms present in electronic devices, the forms of contamination and the control methods reported in the literature. From this review, it was possible to perceive the potential for carrying microorganisms and propagating infectious diseases present in these objects. These are contaminated through direct contact with the skin or by salivary droplets. The residence time can vary from days to months depending on the microorganism and the material of the surface composition. As a means of prevention and control, resources such as coating films, based on nanotechnology, that present antimicrobial activity, aiming to limit the spread of microorganisms, are already available on the market. However, the search for chemical agents intended for use in electronic devices presents scarce data. From this study, the importance of preventive measures and care in the use of objects that can be possible vehicles for the transmission of pathogens is understood, indicating the asepsis of the hands before and after the use of electronic devices and also the use of coating films with antimicrobial activity, the recommendation of alcohol and other chemical substances, despite their proven efficacy, must be carefully evaluated and the recommendations of the manufacturers of electronic devices must be followed.